2019
DOI: 10.1017/jfm.2019.991
|View full text |Cite
|
Sign up to set email alerts
|

Liquid velocity fluctuations and energy spectra in three-dimensional buoyancy-driven bubbly flows

Abstract: We present a direct numerical simulation (DNS) study of pseudo-turbulence in buoyancy driven bubbly flows for a range of Reynolds (Re) and Atwood (At) numbers. We study the probability distribution function of the horizontal and vertical liquid velocity fluctuations and find them to be in quantitative agreement with the experiments. The energy spectrum shows the k −3 scaling at high Re and becomes steeper on reducing the Re. To investigate the spectral transfers in the flow, we derive the scale-by-scale energy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 38 publications
8
56
0
Order By: Relevance
“…As reviewed in Ref. [7] and the recent DNS work [91], this scaling is robust and is observed for a homogeneous bubble swarm for a wide range of parameters: 10 ≤ Re bub ≤ 1000 and 1 ≤ We ≤ 4 where We is the Weber number. In contrast, point particle simulations do not show k −3 scaling [25], because the wakes behind the bubbles are crucial for the emergence of a -3 scaling (in both frequency or wavenumber space) [7].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…As reviewed in Ref. [7] and the recent DNS work [91], this scaling is robust and is observed for a homogeneous bubble swarm for a wide range of parameters: 10 ≤ Re bub ≤ 1000 and 1 ≤ We ≤ 4 where We is the Weber number. In contrast, point particle simulations do not show k −3 scaling [25], because the wakes behind the bubbles are crucial for the emergence of a -3 scaling (in both frequency or wavenumber space) [7].…”
Section: Introductionsupporting
confidence: 54%
“…This means that the inverse of scalar diffusive time scale needs to be around the onset frequency of -3 subrange. A direct verification on the speculation may be done by the investigation on the diffusive, spectral transfer budgets of the spectral content of scalar fluctuations at the -3 subrange that can be analysed by direct numerical simulations similar to [91]. Another future investigation is to predict the critical α that leads to the saturation of the -3 scaling in passive scalar spectra for a general turbulent bubbly thermal mixing layer (for different incident turbulent intensities, mean temperature gradient forcing and high-Re bubble properties).…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, the very recent numerical results presented by Pandey et al (2020) are also shown for two Ar numbers. It is worth recalling that these results have been obtained with a lower resolution (24 points per diameter instead of 82 for the present simulation), and using a much lower density ratio of approximately 20, instead of 800 for the present simulation as for water/air.…”
Section: Three-dimensional Bubble Columnmentioning
confidence: 98%
“…Furthermore, in the first work (Roghair et al 2011) realistic physical properties are chosen but just a few bubbles are released, of the order of 10, while in the study by Pandey et al (2020) many bubbles are followed but with a very low density ratio between the fluid and the gas, between 1.1 and 20. The nonlinear interactions among bubbles are, however, key to the dynamics and their statistical study requires the presence of a large number of bubbles (Lance & Bataille 1991;Risso 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation